Comparative Bioavailability of Amphetamine Extended-Release Oral Suspension and Extended-Release Mixed Amphetamine Salts. (April 2021) - Pardo, Antonio; Bouhajib, Mohammed; Rafla, Eman; King, Thomas R.; Kando, Judith C.
Abstract: Purpose: This open-label, single-dose, randomized, two-period, two-treatment, two-sequence, crossover study evaluated the comparative bioavailability between amphetamine extended-release oral suspension (treatment A: AMPH EROS, Dyanavel XR 2.5 mg/mL, 18.8 mg amphetamine base per 7.5 mL) and extended-release mixed amphetamine salts (treatment B: ER MAS, Adderall XR 30 mg capsules, equivalent to 18.8 mg amphetamine base per capsule) after a single dose in healthy adult subjects, under fasted conditions. Methods: The crossover design allowed for intra-subject PK comparisons. Relative comparable bioavailability was determined by a statistical comparison of the AUC and Cmax parameters for both d- and l-amphetamine, where the geometric mean ratios for AUC and Cmax were within the 90% confidence limits (80.0%–125.0%) to determine comparable bioavailability between test products. Subjects in sequence 1 received treatment A followed by B; subjects in sequence 2 received treatment B followed by treatment A. PK samples were obtained at 0 (pre-dose) through 60 hours post-dose. The safety assessment was based on reported frequency and severity of adverse events. Results: Thirty (30) subjects were enrolled and 28 completed. The mean age of subjects was 35 years, with a mean BMI of 25.9 kg/m2. Most subjects were Male (63.3%) and Black (56.7%). The geometric mean ratios for Cmax and all AUC measurements were within the 80–125% bound indicating comparable bioavailability between both test products. Both test products were generally well-tolerated with no serious AEs reported. Conclusions: The bioavailability of a single 7.5 mL dose of AMPH EROS 2.5 mg/mL was comparable to a single 30 mg capsule dose of ER MAS. AMPH EROS (both d- and l-amphetamine) showed equivalent peak and overall exposure to ER MAS under fasted conditions. Funding: Tris Pharma, Inc.